The gender and ethnic characteristics of internet content consumption among student youth in Kyzyl and Krasnoyarsk - Yaskevich, Roman A.; Fedorova, Angelica A.; Kostyuchenko, Yulia R. (The New Research of Tuva, 2024)
The article analyzes the characteristics of the Internet content consumed (gaming, social networks, mixed and undifferentiated internet addiction) among students in Kyzyl and Krasnoyarsk, with different gender and ethnic backgrounds. The analysis is based on the results of a survey conducted among 977 students between September 2022 and May 2023.It was found that students in Kyzyl have a higher prevalence of all types of internet addiction compared to students in Krasnoyarsk. The study also focuses on the influence of ethnic background on the development of different forms of internet addiction among students in Kyzyl. Specifically, it was observed that Tuvan students have a higher frequency of consuming various types of internet content, including gaming (11.1% vs. 10.2%), social networking (9.2% vs. 6.4%), and undifferentiated addiction (12.3% vs. 10.6%).Gender differences in the prevalence of different types of internet addiction have been identified: gaming and combined addiction are more common among Tuvan boys, while social network and unspecified addiction are more prevalent among Tuvan girls.
Keywords: student; Tuva; Kyzyl; Krasnoyarsk; internet; internet addiction; consumed content; Tuvans; Russians